The Comparison of Waria Conversion Registered in Padang City and Sungai Penuh City - Nasri, Dedi Saputra; Tulanggung, Ermanto; Duerawee, Abdulkarim (Universitas Ahmad Dahlan, 2022)
This study aims to describe and explain the comparison of conversation registers used by transgender communities in two different cities, namely Padang City and Sungai Full City. This research is a qualitative research using descriptive method. This research was conducted in Padang City, West Sumatra Province and Sungai Penuh City, Jambi Province. The data of this research are utterances containing transgender registers in the city of Padang and the city of Sungai Penuh. The data in this study were collected using the tapping method that utilizes advanced techniques in the form of recording techniques and note-taking techniques. The findings of the study were that 160 transgender conversation register data were found in the City of Padang and the City of Sungai Penuh in terms of 2 domains, namely words, phrases and sentences. In the realm of words, it is divided into adjectives (adjectives), verbs (verbs), nouns (nouns) and greeting words. In the realm of phrases, it is divided into noun phrases, verb phrases, and adjective phrases. Overall, the similarities of the transgender registers of Padang City and Sungai Penuh City are very visible because they use the same vocabulary, namely from the vocabulary of waria in Indonesia. On the other hand, the comparison of conversation registers is clearly seen from the effect of using regional languages ​​attached to speakers and the places that become a thing in an area